2018
DOI: 10.1080/19393555.2018.1426799
|View full text |Cite
|
Sign up to set email alerts
|

An automatic cryptanalysis of simple substitution ciphers using compression

Abstract: Automatic recognition of correct solutions as a result of a ciphertext only attack of simple ciphers is not a trivial issue and still remains a taxing problem. A new compression based method for the automatic cryptanalysis of simple substitution ciphers is introduced in this paper. In particular, this paper presents how a Prediction by Partial Matching ('PPM') text compression scheme, a method that shows a high level of performance when applied to different natural language processing tasks, can also be used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Subsequently, two models with and without update exclusion were created using the BSK to see which one worked better in calculating the codelength (Sub-stage 2c). The results are presented below in Table 4: The results of these different experiments revealed that the language model without update exclusion performed better than the model with update exclusion, which is compatible with the findings of Al-kazaz for cryptanalysis [60].…”
Section: Sub-stage 2a: Statistical Stagesupporting
confidence: 83%
“…Subsequently, two models with and without update exclusion were created using the BSK to see which one worked better in calculating the codelength (Sub-stage 2c). The results are presented below in Table 4: The results of these different experiments revealed that the language model without update exclusion performed better than the model with update exclusion, which is compatible with the findings of Al-kazaz for cryptanalysis [60].…”
Section: Sub-stage 2a: Statistical Stagesupporting
confidence: 83%
“…viii. Playfair cipher is vulnerable to statistical analysis attack and several successful attacks such as [17]- [19] have been reported.…”
Section: Overview Of Playfair Ciphermentioning
confidence: 99%